2019
DOI: 10.1111/vco.12462
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue sarcoma in dogs: A treatment review and a novel approach using electrochemotherapy in a case series

Abstract: Canine soft tissue sarcomas (STSs) are locally invasive mesenchymal neoplasms. Electrochemotherapy (ECT) is an antitumour local ablative treatment that uses electric pulses to enhance the intracellular delivery of cytotoxic drugs. The aim of this retrospective study was to review the current treatment for STSs and to evaluate the efficacy and safety of ECT with bleomycin in canine STSs. Fifty‐two dogs with 54 STSs were included. Three groups were arranged: (a) ECT alone, (b) intra‐operative ECT and (c) adjuvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…Generally, ECT/GET treatments are well-tolerated, with most of the dogs in all studies maintaining their normal habits and routines ( 56 , 64 , 65 , 70 , 71 , 85 , 87 ). Conversely, Torrigiani et al ( 34 ) reported higher local treatment toxicity if a higher amplitude to electric distance ratio (1,200 vs. 1,000 V/cm) was used with type II needle electrodes. However, the possible post-treatment complications can be considered much less severe than those of surgery for oral tumors ( 79 ) or radiotherapy ( 89 , 90 ).…”
Section: Concluding Recommendations On Electroporation-based Treatmenmentioning
confidence: 97%
See 2 more Smart Citations
“…Generally, ECT/GET treatments are well-tolerated, with most of the dogs in all studies maintaining their normal habits and routines ( 56 , 64 , 65 , 70 , 71 , 85 , 87 ). Conversely, Torrigiani et al ( 34 ) reported higher local treatment toxicity if a higher amplitude to electric distance ratio (1,200 vs. 1,000 V/cm) was used with type II needle electrodes. However, the possible post-treatment complications can be considered much less severe than those of surgery for oral tumors ( 79 ) or radiotherapy ( 89 , 90 ).…”
Section: Concluding Recommendations On Electroporation-based Treatmenmentioning
confidence: 97%
“…Torrigiani et al ( 34 ) also treated non-metastatic soft tissue sarcomas in dogs with ECT. Of 52 dogs with 54 spontaneous soft tissue sarcomas, five had a (non-oral) tumor on the head without further specification of the exact location.…”
Section: Electroporation-based Treatments For Oral and Maxillofacial mentioning
confidence: 99%
See 1 more Smart Citation
“…The recurrence rate in groups that were treated with electrochemotherapy during or after surgery was similar (23% and 25%). 94 In another study, in addition to an intravenous administration of bleomycin, the tumor bed was also infiltrated with cisplatin. This combination was very effective, 26 of 30 dogs were without evidence of recurrence, and the median estimated disease-free interval was 857 days.…”
Section: Studies In Veterinary Oncologymentioning
confidence: 99%
“…The results of electrochemotherapy treatment of two large cohorts of dogs with soft tissue sarcoma were recently published. In a study by Torrigiani et al, 94 52 dogs with 54 soft tissue sarcomas were treated either with electrochemotherapy with bleomycin alone, during open surgery, or with electrochemotherapy as an adjuvant to surgery. The recurrence rate in groups that were treated with electrochemotherapy during or after surgery was similar (23% and 25%).…”
Section: Studies In Veterinary Oncologymentioning
confidence: 99%